The Pro-poor Policy of Microfinance in Indonesia - Nugroho, Agus Eko (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2009)
This paper discusses and proposes the policy issues associated with the development of microfinance industry in Indonesia. Despite its capability of financing small-scale businesses, the development of the microfinance industry is far behind that of commercial banks. The policy focus on developing sound financial practices of microbanks has ignored the role of semi-formal and informal microfinance institutions (MFIs) in serving poor people. Compliance with the sound banking practices could inevitably drive microbanks away from serving the poor. Regarding the capability of informal and semi-formal MFIs of outreaching the poor, the challenges to microfinance policy in Indonesia is to develop inclusive financial systems through which the progress of microbanks goes in a parallel direction with the developments of semi-formal and informal MFIs, such as cooperatives and rotating saving and credit associations (ROSCAs).